Assessment of written skill in morocco -The sixth year of primary education as a model- - Jaghdoul, Eman Abdullah (Journal of Educational and Psychological Sciences, 2020)
The aim of this research is to introduce the skill of written expression, in terms of the criteria adopted in its evaluation in the sixth section of primary education, given the great controversy and debate that this topic presents. We have relied in this study on the descriptive-analytical method, which we were able to achieve it through a directed questionnaire by a group of Arabic language teachers. This research has led us to reach a set of results, the most important of which is the possibility of one written production for several different evaluations. The thing that urges us to review the criteria adopted in the evaluation, with a view to codifying and controlling them, so that the evaluation eventually leads to accurate and stable results.
Keywords: Assessment; written; Morocco; the sixth section of primary